Expression of Pro‐inflammatory Interleukin‐8 is Reduced by Ayurvedic Decoctions. (6th January 2014) - Guerrini, Alessandra; Mancini, Irene; Maietti, Silvia; Rossi, Damiano; Poli, Ferruccio; Sacchetti, Gianni; Gambari, Roberto; Borgatti, Monica
<x xml:space="preserve">Abstract</x> Eleven decoctions, obtained from indian plants widely used in ayurvedic medicine, have been investigated as a possible source of molecules exhibiting biological activity on the interaction between DNA and NF‐kB, a transcription factor involved in the expression of proinflammatory genes. Cystic fibrosis (CF) cell line stimulated by TNF‐α has been used as inflammatory cellular model to determinate interleukin‐8 (IL‐8), one of the most relevant pro‐inflammatory mediator in CF regulated by the NF‐kB. The chemical characterization of these 11 decoctions by spectrophotometric analysis and NMR fingerprinting highlighted that sugars and polyphenols seemed to be the main compounds. Our results demonstrated that Azadirachta indica, Terminalia bellerica, Terminalia chebula, Hemidesmus indicus, Emblica officinalis and Swertia chirata are the most active decoctions in inhibiting NF‐kB/DNA interactions by EMSA assay and in reducing pro‐inflammatory IL‐ 8 expression in CF cells at IC50 concentrations by Real‐Time and Bio‐plex analyses. Finally, we observed the increase of all inhibitory activities with the rise of total polyphenols, procyanidins and flavonoids, except for the levels of IL‐8 mRNA accumulation, that were as high as flavonoid content grown up by the statistical multivariate analyses. In conclusion, these six decoctions might be interesting to explore new anti‐inflammatory treatments for diseases, such as CF. Copyright © 2014 John Wiley & Sons, Ltd.